2013
DOI: 10.1002/14651858.cd008888.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids for subacute cough in children

Abstract: BackgroundCough is the most common symptom presenting to primary healthcare services. Cough in children is associated with significant morbidity for both children and their parents. While inhaled corticosteroids (ICS) can potentially reduce cough associated with airway inflammation and airway hyper-reactivity, use of ICS in children is not without potential adverse effects. Therefore, it would be beneficial to clinical practice to evaluate the evidence for the efficacy of ICS in reducing the severity of cough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…In recent researches, many of the most common medications used to treat cough are nowadays studied to evaluate not only their efficacy, but also safety, in order to underline how benefits/risks ratio tent toward their beneficial effects [ 6 - 8 ]. In most cases, the pharmacological treatment aims to suppress the symptom (cough suppressant therapy), with synthetic agents that play an inhibitory effect on the cough reflex or act as mucolytic drugs, with the simple intent to reduce both intensity and frequency of cough in the short term, increasing the possibility to experience side effects [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent researches, many of the most common medications used to treat cough are nowadays studied to evaluate not only their efficacy, but also safety, in order to underline how benefits/risks ratio tent toward their beneficial effects [ 6 - 8 ]. In most cases, the pharmacological treatment aims to suppress the symptom (cough suppressant therapy), with synthetic agents that play an inhibitory effect on the cough reflex or act as mucolytic drugs, with the simple intent to reduce both intensity and frequency of cough in the short term, increasing the possibility to experience side effects [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are two SRs regarding the use of inhaled corticosteroids [39, 40]. Among the various selected works, only one trial (which contained serious methodological defects) demonstrated a relatively modest efficacy of fluticasone dipropionate for nocturnal cough [41].…”
Section: Resultsmentioning
confidence: 99%
“…In regard to these latter Cochrane SR references [ 29 - 33 ], our research failed to discover any subsequent noteworthy trials. There are two SRs regarding the use of inhaled corticosteroids [ 39 , 40 ]. Among the various selected works, only one trial (which contained serious methodological defects) demonstrated a relatively modest efficacy of fluticasone dipropionate for nocturnal cough [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ряд исследований и метаанализов, выполненных в последнее время, продемонстрировали отсутствие убедительной эффективности по снижению частоты и выраженности кашля у широкого круга препаратов, традиционно используемых как у детей, так и взрослых [9,[25][26][27][28]. Большая часть работ, подтверждаю щих эффективность той или иной медикаментозной терапии при остром кашле, выполнена несколько десятилетий назад и является низкого качества.…”
Section: проблема лечения острого и подострого кашляunclassified